The atmospheric circulation associated with extreme rainfall events in Piura, Peru, during the 1997-1998 and 2002 El Niño events - Takahashi, Ken (2004)
The lowland of Piura, in northwestern Peru, is very strongly impacted by El Niño. Its climate is arid but can experience very heavy rainfall associated with the high nearby sea surface temperature (SST) during El Niño events. Rainfall, however, tends to occur in discrete, intense events and an understanding of the physical conditions favoring a particular day with heavy rainfall over others is of both scientific and practical interest. In this work, we consider the rainy periods of December 1997 to April 1998 and March to April 2002, corresponding to very strong and weak to moderate El Niño conditions, respectively, and search for systematic differences in the atmospheric circulation that may account for the day-to-day variability of rainfall in Piura. Composites of vertical profiles of winds measured by wind profiling radars in Piura, as well as composites of NCEP/NCAR Reanalysis wind fields, suggest that rainy days are associated with an enhanced onshore westerly low-level flow, which may help the triggering of convection by orographic lifting over the western slope of the Andes. Synoptic control was evident in the rainfall record for 1997-1998 but was not as clear in that of 2002. However, in both periods of study the low-level flow over Piura, which we found to be important for the triggering of rainfall, was modulated by tropical synoptic scale disturbances. The structures of the composited wind differences suggest that they may be related to equatorially trapped tropospheric waves, particularly Kelvin and n=1 Rossby waves.